Pengembangan Model Hybrid Learning pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII SMP Negeri di Indonesia Tahun Pembelajaran 2024/2025 - Juwita Tiara Agista Gulo; Hasudungan Simatupang; Betty A.S Pakpahan; Lince Sihombing; Tahadodo Waruwu (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The purpose of this study was to develop and produce hybrid learning in the subject of Christian Religious Education and Character Education of class VIII of Junior High Schools in Indonesia in the odd semester of the Independent Curriculum. This study uses a development method with the ADDIE approach model. The study was conducted at SMP Negeri 2 Pollung. Data collection used a validation questionnaire and a response questionnaire. The validation questionnaire was used for validator lecturers who are media experts, design experts, material experts, and language experts. The response questionnaire was used for PAK teachers of class VIII of SMP Negeri 2 Pollung and students of class VIII of SMP Negeri 2 Pollung totaling 24 people for small groups and 66 people for large groups. The data analysis techniques used in this study were qualitative descriptive analysis and quantitative descriptive analysis. The results of this study are in the form of hybrid learning media products using PowerPoint in the subject of Christian Religious Education and Character Education of class VIII of SMP in the Odd Semester of the Independent Curriculum. The results of the study indicate that the products made are valid and suitable to be used as learning media. The assessment is based on validation experts, teachers, and students, namely media experts obtained an assessment percentage of 100% (very valid), design experts 96% (very valid), material experts 100% (very valid), language experts 100% (very valid), PAK teachers 100% (very valid), and finally students in small and large groups obtained an average percentage of 100% (very good).